2011
DOI: 10.1097/jsm.0b013e318221840f
|View full text |Cite
|
Sign up to set email alerts
|

Equestrian Injuries Caused by Horse Kicks: First Results of a Prospective Multicenter Study

Abstract: Hoof kick injuries account for a significant proportion of equine injuries and occur when riders are dismounted, most frequently when grooming without wearing protective equipment. Head and facial injuries occur most frequently and suggest that mandatory helmet and facial grill use should be considered during all horse-related activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 6 publications
3
32
1
1
Order By: Relevance
“…[9] Others have put forward that animal kicks are responsible for 16-58% of animal-related injuries. [2,3,14,[18][19][20]22] Similar to others, our study suggested that the most common injured body regions were the upper and lower extremities. [2,9,15,16,18,19] Head and face, and chest were the second most common injured body regions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[9] Others have put forward that animal kicks are responsible for 16-58% of animal-related injuries. [2,3,14,[18][19][20]22] Similar to others, our study suggested that the most common injured body regions were the upper and lower extremities. [2,9,15,16,18,19] Head and face, and chest were the second most common injured body regions.…”
Section: Discussionsupporting
confidence: 88%
“…Using helmets and face guard reduce the severity of head injury among equestrians. [2,22,24] Those who are riding large animals should use helmets and other protective gears. [23] Legislation plays a role in preventing and reducing injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Journal samples from four major Swedish animal hospitals show that the problem exists according to a preliminary survey by the authors. However, there have been studies on human injuries inflicted by horses (Kriss & Kriss, 1997;Meredith & Antoun, 2011;Eckert et al, 2011) with horse kicks accounting for approx. 10% of these injuries (Meredith & Antoun, 2011).…”
Section: Literature and Preliminary Workmentioning
confidence: 99%
“…Injuries caused by hoof kicks are common and can have serious consequences for horses as well as for humans (Derungs et al, 2004;Eckert et al, 2011). A retrospective study conducted at the Equine Clinic of the Vetsuisse Faculty, University of Zurich, showed that approximately 50% of horses referred because of a kick injury had a bone fracture (Derungs et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This finding coupled with marked soft tissue trauma at the site of injury suggests that the force of a kick from a horse is enormous. Studies on the risk and consequences of kick injuries in people have shown that the mortality rate of kicked equestrians is high and that riding a horse can be more hazardous than motorcycle or car racing (Busch et al, 1986;Exadactylos et al, 2002;Eckert et al, 2011). In a study of equestrian injuries, being kicked by a horse was the second most common cause of injury after falling off a horse (Abu-Zidan and Rao, 2002).…”
Section: Introductionmentioning
confidence: 99%